ANALISIS STRUKTUR KOMUNITAS KEPITING DI KAWASAN MANGROVE STASIUN KELAUTAN UNIVERSITAS RIAU KELURAHAN PURNAMA KOTA DUMAI PROVINSI RIAU - Rozanda, Fenti; Mulyadi, Aras; Nasution, Syafruddin (Fakultas Perikanan dan Kelautan Universitas Riau, 2020)
This research was conducted in January 2019 in the mangrove area of Purnama Village, Dumai City, Riau Province. The purpose of this study was to determine the crab community structure which includes the type, abundance, crab distribution patterns, species diversity (H '), species uniformity (E), and species dominance (C) crabs. The method used in this study is a survey method. There are three observation stations with each of the three transects at each station, on each transect line there is a square plot with a size of 5x5 m2. Crab sampling is done quantitatively and qualitatively. Based on the results of the study it was found that the species of crabs identified at the area of the research were Sesarma reticulatum, S. guttatum, Uca dussumieri, U. rosea, U. vocans, Cardisoma carnifex, and Clistocoeloma merguinse. Furthermore, the abundance of crabs obtained is between 1560-2040 Ind / Ha with cluster distribution patterns. The average value of species diversity (H ') indicates moderate diversity, uniformity (E) indicates high species uniformity, and species dominance value (C) indicates no dominating species.This research was conducted in January 2019 in the mangrove area of Purnama Village, Dumai City, Riau Province. The purpose of this study was to determine the crab community structure which includes the type, abundance, crab distribution patterns, species diversity (H '), species uniformity (E), and species dominance (C) crabs. The method used in this study is a survey method. There are three observation stations with each of the three transects at each station, on each transect line there is a square plot with a size of 5x5 m2. Crab sampling is done quantitatively and qualitatively. Based on the results of the study it was found that the species of crabs identified at the area of the research were Sesarma reticulatum, S. guttatum, Uca dussumieri, U. rosea, U. vocans, Cardisoma carnifex, and Clistocoeloma merguinse. Furthermore, the abundance of crabs obtained is between 1560-2040 Ind / Ha with cluster distribution patterns. The average value of species diversity (H ') indicates moderate diversity, uniformity (E) indicates high species uniformity, and species dominance value (C) indicates no dominating species.